Reformasi Administrasi Publik pada Digitalisasi Pelayanan Surat Izin Mengemudi (SIM) - Elizabeth Girsang; Eko Prasojo (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Driving license (SIM) is proof of registration and identification for a person who has met the administrative requirements, is physically and mentally healthy, as well as proof that the person understands traffic regulations and can drive a motorized vehicle, so it is granted by the Police. Making and renewing SUM is carried out at the Office of the SIM Administration Executing Unit (Satpas) which are available in several locations in each region, and when obtaining a SIM cannot be represented by someone else. There were problems in managing SIMs, one of which was extortion, which then triggered the implementation of administrative reforms towards digitizing services. There are three main principles in practice in preventing extortion in licensing and non-licensing, namely predictability, digitizing services and not burdening. Departing from public problems related to SIM services, the Directorate of Registration and Identification (Dit Regident) of Korlantas Polri innovates by utilizing technology.